Hungarian Student Federation in Madrid to the President of the Thirteenth UN General Assembly - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Hungarian Student Association Appeal to the United Nations to do everything in its power to reject the credentials of Hungary's representatives to the UN.